Penerapan Pembelajaran Think Pair Share Untuk Menaikkan Motivasi dan Hasil Belajar - Koyimah Koyimah (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
This study aims to determine the application of the Think Pair Share (TPS) cooperative learning model as an effort to increase motivation and learning outcomes for PAI and BP prayer materials before and after meals. The type of research used is classroom action research (CAR). The subjects of this study were the second grade students of SDN Ciporos as many as 30 students. Data collection techniques using test, observation, and documentation techniques. Validation technique with data triangulation, member check, and audit trail. The data analysis technique used descriptive analysis. The results showed that learning motivation in the initial conditions was 33.33% or 10 students, increased to 56.67% or 17 students and 93.33% or 28 students in the second cycle. The average increase in learning outcomes from 56.00 in the initial conditions to 71.33 and 83.67 in the second cycle with learning mastery of 6 students or 20.00%, increased to 12 students or 40.00% and 90.00% or 27 students in the second cycle